PENGARUH HUBUNGAN ATASAN BAWAHAN (LMX), KEADILAN ORGANISASI DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI BKPSDM BUTON TENGAH - Muksin Muksin; Samdin Samdin; Salma Saleh (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2022)
The Effect of Leader Member Exchange, Organizational Justice and Organizational Commitment on  Employees Performance of BKPSDM Buton Tengah. Human Resource Management Thesis, at the Master of Management Science Study Program, Halu Oleo University Graduate Program. Supervised by Samdin and Salma SalehThe objectives to be achieved in this study are to: examine and explain the simultaneous effect of Leader Member Exchange, organizational justice and organizational commitment on employees performance of BKPSDM Buton Tengah. Testing and explaining the influence of Leader Member Exchange on the performance of Central Buton BKPSDM employees. Organizational Justice on Employees Performance of Central Buton BKPSDM. And Organizational Commitment on  Employees Performance of Central Buton BKPSDM. The population in this study were all employees of BKPSDM Buton Tengah, all of which were civil servants totaling 52 employees. Measurement of data in this study using a Likert scale. The data analysis technique used in this study is descriptive statistical data analysis and inferential statistics, namely multiple linear regression analysis using SPSS Version 20 software. The result of this study showed that Leader Member Exchange, Organizational Justice and Organizational Commitment simultaneously has positif and significant effect on employee performance. Leader Member Exchange has a significant positive effect on employee performance. This means that increasing Leader Member Exchange has a positive contribution to improving employee performance. Organizational Justice has a positive effect on employee performance. This means that the increase in employee organizational justice has a significant contribution to employee performance. Organizational commitment has a positive but not significant effect on employee performance. This means that good organizational commitment makes a positive contribution to improving employee performance but is not significant or not meaningful